Unchain Your Heart: Battling Coronary Artery Disease (International Journal of Current Research in Physiology and Pharmacology, 2023)
ABSTRACTCoronary Artery Disease (CAD) remains a significant contributor to illness and mortality on a global scale. It is characterized by the gradual narrowing of coronary arteries due to the formation of atherosclerotic plaques, leading to a disruption in the blood supply to the heart muscle. This often results in ischemic events such as angina and heart attacks. This summary offers a concise overview of CAD, concentrating on its causes, risk factors, clinical presentation, and contemporary methods of treatment. The development of CAD involves a complex interaction of genetic predisposition, traditional risk factors (such as hypertension and abnormal lipid levels), and lifestyle factors. Despite its subtle beginnings, CAD can show itself through symptoms like angina, breathlessness, or silent ischemia. Early detection is crucial and can be aided by stress tests, coronary angiography, and non-invasive imaging techniques. Approaches to managing CAD encompass adjustments to one's lifestyle, pharmacological interventions, and invasive procedures. Lifestyle changes involve dietary improvements, physical activity, and smoking cessation, all of which have been proven to slow down the progression of CAD. Medications like antiplatelets, statins, and beta-blockers target risk factors and alleviate symptoms. Invasive treatments such as percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) restore blood flow, leading to better quality of life and increased survival rates. In conclusion, the widespread occurrence of CAD and its clinical implications highlight the importance of proactive prevention and evidence-based treatment. Advances in diagnostic methods and therapeutic approaches continue to shape the management of CAD, leading to improved outcomes and instilling optimism in the fight against this challenging cardiovascular condition.Keywords: Heart, Coronary artery, Lifestyle, medications.
Keywords: Heart, Coronary artery, Lifestyle, medications